Characterization of the far-red fluorescent probe MitoView 633 for dynamic mitochondrial membrane potential measurement - Ernst, Patrick; Kim, Seulhee; Yang, Zengqiao; Liu, Xiaoguang Margaret; Zhou, Lufang (Frontiers in Physiology, 2023)
MitoView 633, a far-red fluorescent dye, exhibits the ability to accumulate within mitochondria in a membrane potential-dependent manner, as described by the Nernst equation. This characteristic renders it a promising candidate for bioenergetics studies, particularly as a robust indicator of mitochondrial membrane potential (∆Ψm). Despite its great potential, its utility in live cell imaging has not been well characterized. This study seeks to characterize the spectral properties of MitoView 633 in live cells and evaluate its mitochondrial staining, resistance to photobleaching, and dynamics during ∆Ψm depolarization. The co-staining and imaging of MitoView 633 with other fluorophores such as MitoSOX Red and Fluo-4 AM were also examined in cardiomyocytes. Spectrum analysis showed that MitoView 633 emission could be detected at 660±50 nm, and exhibited superior thermal stability compared to tetramethylrhodamine methyl ester (TMRM), a commonly used ∆Ψm indicator, which emits at 605±25 nm. Confocal imaging unequivocally illustrated MitoView 633's specific localization within the mitochondrial matrix, corroborated by its colocalization with MitoTracker Green, a well-established mitochondrial marker. Furthermore, our investigation revealed that MitoView 633 exhibited minimal photobleaching at the recommended in vitro concentrations. Additionally, the dynamics of MitoView 633 fluoresce during carbonyl cyanide-p-trifluoromethoxyphenylhydrazone (FCCP, a mitochondrial uncoupler)-induced ∆Ψm depolarization mirrored that of TMRM. Importantly, MitoView 633 demonstrated compatibility with co-staining alongside MitoSOX Red and Fluo-4 AM, enabling concurrent monitoring of ∆Ψm, mitochondrial ROS, and cytosolic Ca 2+ in intact cells. These findings collectively underscore MitoView 633 as a superb molecular probe for the singular or combined assessment of ∆Ψm and other indicators in live cell imaging applications.